Pemantauan Status Gizi Melalui Program Penjaringan Kesehatan Anak Sekolah Dasar di Kota Sibolga - Bibi Ahmad Chahyanto; Hasfika, Ivonna (Kabar Gizi Indonesia, 2024)
Health Screening Program for School Children’s is an effort by the government to detect nutrition and health problems in school children as early as possible. The results of anthropometric measurements from this program can be further processed into community nutritional assessment and become material for determining policies for elementary school children's nutrition programs. This study aims to describe and analyze the results of the nutritional assessment of elementary school children’s in Sibolga City. The method used was analytical observational with a cross-sectional research design. The data was obtained from the results of anthropometric measurements in the health screening activities of grade 1st elementary school and islamic elementary school children in Sibolga City in the 2017/2018 and 2018/2019 academic years. Data processing and analysis was carried out in January – July 2023. The results showed that not all schools and students participating in the health screening program can use their data in assessing nutritional status. The highest prevalence of nutritional status was normal nutritional status, however, problems of malnutrition, undernutrition, overnutrition and obesity are still found with various prevalence rates. Gender was not related to the nutritional status of elementary school children (p=0,871), while school status was significant related to the nutritional status of elementary school children (p=0,000). This activity shows that the health screening program for school children’s was very important and the results can be further analyzed into periodic nutritional status monitoring data.